Foundations of Library and Information Science, 4thed. - Satija, Mohinder P. (International Journal of Knowledge Content Development & Technology, 2016)
Over the last century the Library and Information Science (LIS) discipline has developed It is so much so that the textbook writers writing on its specialized areas such as knowledge organization, digital libraries, library effectiveness or library users, to name a few. as though hardly anyone is interested, even competent, a general or sufficiently advanced textbook covering the entire field1. eneralists in the LIS field have become specialists Therefore, this book is welcome. The fact that it is in its fourth edition (earlier editions were published in 2000, 2004 and by Neal-Schuman, USA) sufficiently indicates its continuing value and acceptance by the profession at large. The book has been published by two outstanding publishers, namely Facet, London and the American Library Association which endows it with a brand value and much authenticity. This rather voluminous text has been contained in ten logically ordered chapters, starting from broader aspects of a library and its social and intellectual environment, and going on to the much more specialized but multidisciplinary topics of information policies and intellectual freedom. In addition, there are four appendices describing major library and information science associations in the USA and IFLA, listing ALA accredited library schools in the US, addressing ALA standards for accreditation of library schools, and lastly containing the Unesco/IFLA manifesto (1994) on public libraries. The text can broadly be divided into two parts. The first part, consisting of five chapters, mostly dwells on library related issues. These chapters progressively discuss the knowledge infrastructure of the society social history of libraries (mostly of the USA) and their mission, the library as a social institution, kinds of libraries and their services, the impact of technology on libraries and library services, and LIS as a profession. It views the libraries in tandem with other memory institutions, namely archives museums . This integrative approach broadens the perspective of libraries as social and cultural institutions and as a collective social memory. Chapter 6 on the organization of knowledge both the twin fields. The other four chapters of the second part mostly dwell on information science and policies. The long chapter on the nature and evolution of information science discusses and describes its relation with librarianship. The chapter on knowledge organization discusses up-to-date techniques and methods for describing information, its representation and retrieval in the traditional print libraries and the e-environment as well. The remaining chapters essentially deal with information policies and their stakeholders, intellectual freedom, right to information, censorship and the ethics of the LIS profession. In the preface the author sets out six articulated purposes, namely a broad introduction to the entire field, major current issues of the discipline, place of the library in the larger social, political and cultural contexts, a guide to search deeper into the LIS studies with the help of references and carefully selected up-to-date reading lists given at the end of each chapter. These reading lists, which have been divided into articles and books/monographs, are a very valuable feature of this text. Though mostly biased to the US situations, the book is a standard work broader but sufficiently detailed introduction to the LIS field in general. It provides good reading and an informative guide for the teachers and new entrants to the LIS profession the world over to help them get to know and learn the scope, nature, objectives, mission and methods of the library and information services. To every chapter is divided into numbered sections with apt feature headings. The text is seasoned with numerous figures and to illustrate the concepts. The book, marked by clarity of thought and expression, is encyclopedic both in scope and function as is evident from the 14-page index, which in itself is a piece of professional work. It lucidly explains and sufficiently discusses thousands of major and minor concepts and methods and issues with authority, and quotes other authorities wherever needed. That is indeed. he author has a of making axiomatic generalizations such as: “Libraries of all types serve a critical function in our society” (p.157); “The information environment grows more complex every year” (p.338) has the insight to make wise statements: “… The best way to combat a bad idea is not to suppress it but to produce a better idea.” (p.491); Tolerance has a complementary relationship to truth. (p.540). In addition he tenders practical advice such as: “Public institutions today must demonstrate their value to citizens and to funders if they expect support” (p.145). All of these make the book engaging, lucid and reliably informative. May the book be kept up-to-date for generations and generations of future LIS. In the preface the author sets out six articulated purposes, namely a broad introduction to the entire field, major current issues of the discipline, place of the library in the larger social, political and cultural contexts, a guide to search deeper into the LIS studies with the help of references and carefully selected up-to-date reading lists given at the end of each chapter. These reading lists, which have been divided into articles and books/monographs, are a very valuable feature of this text. Though mostly biased to the US situations, the book is a standard work broader but sufficiently detailed introduction to the LIS field in general. It provides good reading and an informative guide for the teachers and new entrants to the LIS profession the world over to help them get to know and learn the scope, nature, objectives, mission and methods of the library and information services. To every chapter is divided into numbered sections with apt feature headings. The text is seasoned with numerous figures and to illustrate the concepts. The book, marked by clarity of thought and expression, is encyclopedic both in scope and function as is evident from the 14-page index, which in itself is a piece of professional work. It lucidly explains and sufficiently discusses thousands of major and minor concepts and methods and issues with authority, and quotes other authorities wherever needed. That is indeed. he author has a of making axiomatic generalizations such as: “Libraries of all types serve a critical function in our society” (p.157); “The information environment grows more complex every year” (p.338) has the insight to make wise statements: “… The best way to combat a bad idea is not to suppress it but to produce a better idea.” (p.491); Tolerance has a complementary relationship to truth. (p.540). In addition he tenders practical advice such as: “Public institutions today must demonstrate their value to citizens and to funders if they expect support” (p.145). All of these make the book engaging, lucid and reliably informative. May the book be kept up-to-date for generations and generations of future LIS. Note: 1. Shera, Jesse H. Introduction to Library Science. Littleton, Colo: Libraries Unlimited, 1976. 2. Chowdhry, G.G. et al. Librarianship: an Introduction. London: Facet Publishing, 2008, 329 p. URL: http://ijkcdt.net/xml/06779/06779.pdf